A consensus list of ultrasound competencies for graduating emergency medicine residents. Issue 6 (21st November 2022) - Haidar, David A.; Peterson, William J.; Minges, Patrick G.; Carnell, Jennifer; Nomura, Jason T.; Bailitz, John; Boyd, Jeremy S.; Leo, Megan M.; Liu, E. Liang; Duanmu, Youyou; Acuña, Josie; Kessler, Ross; et al.
Abstract: Objectives: Emergency ultrasound (EUS) is a critical component of emergency medicine (EM) resident education. Currently, there is no consensus list of competencies for EUS training, and graduating residents have varying levels of skill and comfort. The objective of this study was to define a widely accepted comprehensive list of EUS competencies for graduating EM residents through a modified Delphi method. Methods: We developed a list of EUS applications through a comprehensive literature search, the American College of Emergency Physicians list of core EUS benchmarks, and the Council of Emergency Medicine Residency‐Academy of Emergency Ultrasound consensus document. We assembled a multi‐institutional expert panel including 15 faculty members from diverse practice environments and geographical regions. The panel voted on the list of competencies through two rounds of a modified Delphi process using a modified Likert scale (1 = not at all important, 5 = very important) to determine levels of agreement for each application—with revisions occurring between the two rounds. High agreement for consensus was set at >80%. Results: Fifteen of 15 panelists completed the first‐round survey (100%) that included 359 topics related to EUS. After the first round, 195 applications achieved high agreement, four applications achieved medium agreement, and 164 applications achieved low agreement. After the discussion, we removed three questions and added 13 questions. Fifteen of 15 panelists completed the second round of the survey (100%) with 209 of the 369 applications achieving consensus. Conclusion: Our final list represents expert opinion on EUS competencies for graduating EM residents. We hope to use this consensus list to implement a more consistent EUS curriculum for graduating EM residents and to standardize EUS training across EM residency programs.